Stability of zircon and its isotopic ratios in high-temperature fluids: long-term (4 months) isotope exchange experiment at 850°C and 50 MPa - Bindeman, Ilya; Schmitt, Axel Karl (Frontiers in Earth Science, 2018)
Stability of zircon in hydrothermal fluids and vanishingly slow rates of diffusion identify zircon as a reliable recorder of its formation conditions in recent and ancient rocks. Debate, however, persists on how rapidly oxygen and key trace elements (e.g., Li, B, Pb) diffuse when zircon is exposed to hot aqueous fluids. Here, we report results of a nano- to micrometer-scale investigation of isotopic exchange using natural zircon from Mesa Falls Tuff (Yellowstone) treated with quartz-saturated, isotopically (18O, D, 7Li, and 11B) labeled water with a nominal δ18O value of +450‰ over 4 months at 850°C and 50 MPa. Frontside (crystal rim inwards) δ18O depth profiling of zircon by magnetic sector SIMS shows initially high but decreasing 18O/16O over a ~130 nm non-Fickian profile, with a decay length comparable to the signal from surficial Au coating deposited onto zircon. In contrast, backside (crystal interior outwards) depth profiling on a 2-3 µm thick wafer cut and thinned from treated zircon by focused ion beam (FIB) milling lacks any significant increase in 18O/16O during penetration of the original surface layer. Near-surface time-of-flight (TOF-SIMS) frontside profiles of uncoated zircon from 4-month and 1-day-long experiments as well as untreated zircons display similar enrichments of 18O over a distance of ~20 nm. All frontside 18O profiles are here interpreted as transient surface signals from nm-thick surface enrichment or contamination unrelated to diffusion. Likewise, frontside depth profiling of H, Li, and B isotopes are similar for long- and short-duration experiments. Additionally, surface U-Pb dating of zircon from the 4-month experiment returned U-Pb ages by depth profiling with ~1 µm penetration that were identical to untreated samples. Frontside and backside depth-profiling thus demonstrate that diffusive 18O enrichment in the presence of H2O is much slower than predicted from experiments in Watson and Cherniak (1997). Instead, intracrystalline exchange of oxygen between fluid and zircon in wet experimental conditions with excess silica occurred over length-scales equivalent to those predicted for dry diffusion. Oxygen diffusion coefficients even under wet conditions and elevated temperatures (850 °C) are <1-3×10-23 m2/sec, underscoring a virtual lack of oxygen diffusion and an outstanding survivability of zircons
Im Titel ist das Gradzeichen in 850°C hochgestellt
Gesehen am 04.09.2019